The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1353/pbm.2007.0020
|View full text |Cite
|
Sign up to set email alerts
|

Racialized Genetics and the Study of Complex Diseases: The Thrifty Genotype Revisited

Abstract: Current debate on the use of population genetic data for complex disease research is driven by the laudable goals of disease prevention and harm reduction for all, especially dispossessed, formerly enslaved, or colonized populations. This article examines one of the oldest gene-based theories of complex disease causation: the thrifty genotype hypothesis (THG). This hypothesis is emblematic of the way in which genetic research into complex disease attracts a high investment of scientific resources while contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 122 publications
0
49
0
Order By: Relevance
“…Prior to 10,000 years ago, all modern humans subsisted as hunter-gatherers who likely experienced frequent cycles of feast and famine. According to the thrifty gene hypothesis, ancestral genetic variants that once promoted the efficient absorption, storage, or utilization of nutrients in this ancestral environment are now maladaptive in more modern environments, increasing risk for disease (51,153). Although genetic evidence for this hypothesis has been inconclusive (34,68,214), recent data from the Macaque Genome Project indicated that a number of polymorphisms in the macaque correspond to known disease-predisposing alleles in humans (39).…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Prior to 10,000 years ago, all modern humans subsisted as hunter-gatherers who likely experienced frequent cycles of feast and famine. According to the thrifty gene hypothesis, ancestral genetic variants that once promoted the efficient absorption, storage, or utilization of nutrients in this ancestral environment are now maladaptive in more modern environments, increasing risk for disease (51,153). Although genetic evidence for this hypothesis has been inconclusive (34,68,214), recent data from the Macaque Genome Project indicated that a number of polymorphisms in the macaque correspond to known disease-predisposing alleles in humans (39).…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Substantial growth and development is completed before birth, as demonstrated by the inverse relationship between birth weight and risk of diabetes and metabolic syndrome later in life [30][31][32]. The thrifty phenotype hypothesis proposes that early-life metabolic adaptations promote survival, with the developing organism responding to environmental cues by selecting an appropriate growth trajectory [33,34].…”
Section: Thrifty Genotype and Phenotype Hypothesismentioning
confidence: 99%
“…Concerns include: how personal genetic data will be stored and used, including for research or 'direct marketing' of products; whether the police or governments will be given access to commercial genetic databases (Kaye 2006); and whether people will be required to reveal genetic test results to insurers or employers (Wallace 2005b). In addition, studies of the genetics of diet-related disease and appetite can detract from the social and economic factors that lead to poor health in marginalised populations (Montana 2007;Paradies et al 2007). Unless genetic testing is genuinely useful to guide treatment, promoting genetic explanations for diet-related disease can be counter-productive -wrongly implying that nothing can be done to change the situation.…”
Section: Limitations Of Personalised Nutritionmentioning
confidence: 99%